Quantitative Effects on Proximal Joints of Botulinum Toxin Treatment for Gastrocnemius Spasticity: A 4-Year-Old Case Study - Veronica Cimolin; Manuela Galli; Marcello Crivellini; Giorgio Albertini (Case Reports in Medicine)
Botulinum toxin A (BTA) is a recognized treatment for the early management of spasticity in children with Cerebral Palsy. This study quantified with Gait Analysis (GA) the gait pattern of a 4-year-old diplegic child with calf contracture before, 5 days, and 3 months after BTA injections into gastrocnemius. Kinematic and kinetic data of main lower limb joints were investigated. After only 5 days, ankle dorsi-plantarflexion and knee flex-extension improved, but hip joint worsened, increasing its excessive flexion, to compensate the improvement in knee position of the treated limb and to obtain better stability. A worsening of hip power happened. After 3 months, all joints generally improved their position during gait cycle. Hip and knee joints increased their range of movement and improvements occurred at ankle kinematics and kinetisc, too; a better ankle position and an increase of its capacity of propulsion during terminal stance were evident.